2014
DOI: 10.1177/1359105314532971
|View full text |Cite
|
Sign up to set email alerts
|

‘You can’t be forcing food down ‘em’: Nursing home carers’ perceptions of residents’ dining needs

Abstract: Malnutrition is a life-threatening condition among older people living in nursing care homes. This qualitative analysis of interview data from five care staff aimed to understand their perceptions of 'caring for' residents' nutritional needs. Tensions in the delivery of care and institutionalisation and disempowerment were identified. Despite carers' good intentions, they often failed to recognise the importance of the psychosocial aspects of mealtimes. Staff shortages, routine-driven, medically based working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 24 publications
7
25
0
Order By: Relevance
“…The participants were aware of this and emphasised the value of becoming familiar and developing relationships aiming to understand individual preferences and needs for nutritional care, although they noted that they lacked the time and capacity to put this into practice. This is in line with the findings in another study where healthcare providers in nursing homes experienced that the quality of the psychosocial aspects of the nutritional care was constrained by the demands of routine-driven, task-oriented practices (39) . Lack of time was repeatedly identified as an issue among our participants and is a well-established barrier for quality nutritional care (20,21,40,41) .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The participants were aware of this and emphasised the value of becoming familiar and developing relationships aiming to understand individual preferences and needs for nutritional care, although they noted that they lacked the time and capacity to put this into practice. This is in line with the findings in another study where healthcare providers in nursing homes experienced that the quality of the psychosocial aspects of the nutritional care was constrained by the demands of routine-driven, task-oriented practices (39) . Lack of time was repeatedly identified as an issue among our participants and is a well-established barrier for quality nutritional care (20,21,40,41) .…”
Section: Discussionsupporting
confidence: 89%
“…Lack of time was repeatedly identified as an issue among our participants and is a well-established barrier for quality nutritional care (20,21,40,41) . Studies have reported that healthcare professionals experience a tension between 'person-centredness' and 'the system' because hectic work and structural barriers negatively affect their ability to provide quality person-centred nutritional care (19,20,(39)(40)(41) .…”
Section: Discussionmentioning
confidence: 99%
“…27 At the same time, mealtimes were highlighted as putting particular strain on the provision of care, with staff commenting that there was a lack of organizational support at mealtimes and that they felt pressured to complete routine tasks during long shifts. 27,31 Member of staff e "Doing a twelve hour shift . three days, all after each other .…”
Section: Organizational and Staff Supportmentioning
confidence: 99%
“…You just wish that you could have a bit of extra help [more staff]". (Dunn and Moore, p.5) 31 It was acknowledged that staff have multiple duties but, at mealtimes, may do little more than serve the food. 34 Time demands, shift changes and a poor relationship between staff was also associated with a breakdown in communication between staff at mealtimes.…”
Section: Organizational and Staff Supportmentioning
confidence: 99%
“…Marcus-Varwijk et al [35] found that it was important for older adults to get to know their healthcare professionals and to build a relationship of trust to be able to discuss lifestyle issues such as nutritional needs and food habits. However, studies commonly report that healthcare providers find that the organisation and structure of care, such as lack of time and resources, lack of nutritional knowledge and skill and lack of communication between services, limit their ability to provide individualised nutritional care to older people in care settings [13,[36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%